Rapid evolution and plasticity of genitalia. (25th September 2020) - Dale Broder, E.; Ghalambor, Cameron K.; Handelsman, Corey A.; Ruell, Emily W.; Reznick, David N.; Angeloni, Lisa M.
Abstract: Genital morphology exhibits tremendous variation and is intimately linked with fitness. Sexual selection, nonmating natural selection and neutral forces have been explored as potential drivers of genital divergence. Though less explored, genitalia may also be plastic in response to the developmental environment. In poeciliid fishes, the length of the male intromittent organ, the gonopodium, may be driven by sexual selection if longer gonopodia attract females or aid in forced copulation attempts or by nonmating natural selection if shorter gonopodia allow predator evasion. The rearing environment may also affect gonopodium development. Using an experimental introduction of Trinidadian guppies into four replicate streams with reduced predation risk, we tested whether this new environment caused the evolution of genitalia. We measured gonopodium length after rearing the source and introduced populations for two generations in the laboratory to remove maternal and other environmental effects. We split full‐sibling brothers into different rearing treatments to additionally test for developmental plasticity of gonopodia in response to predator cues and food levels as well as the evolution of plasticity. The introduced populations had shorter gonopodia after accounting for body size, demonstrating rapid genital evolution in 2–3 years (8–12 generations). Brothers reared on low food levels had longer gonopodia relative to body size than those on high food, reflecting maintenance of gonopodium length despite a reduction in body size. In contrast, gonopodium length was not significantly different in response to the presence or absence of predator cues. Because the plastic response to low food was maintained between the source and introduced populations, there was no evidence that plasticity evolved. This study demonstrates the importance of both evolution and developmental plasticity in explaining genital variation. Abstract : Male Trinidadian guppies introduced to replicate streams with reduced predation risk evolved shorter gonopodia (after accounting for body size), demonstrating rapid genital evolution in 2–3 years (8–12 generations).